Evaluation of Inclusion Thematic Class in Special Needs Students at SD Barusari 01 Semarang - Mas’ut, Bilal lutfi; Purwadi, Purwadi; Mudzanatun, Mudzanatun (Journal of Education Reseach and Evaluation, 2019)
The purpose of this study was to find out how the implementation of inclusive class thematic learning, especially in terms of planning, implementation, and evaluation of learning outcomes in students with special needs SD Barusari 01 Semarang. The research method used is a qualitative descriptive method. Based on the results of data analysis and discussion it can be concluded that in terms of planning of learning carried out by the teacher includes planning in the form of syllabus, rpp, preparation of learning media and approaches taken by the teacher which later makes ABK students feel comfortable in attending the lesson well planned. The results of the analysis plan for the implementation of thematic learning with a percentage of 99%. For the implementation of learning it is also well implemented, can be seen from teaching and learning activities between teachers and students both in theory and practice mutually supportive. The results of the analysis of the implementation of thematic learning reached a percentage of 85%. For evaluation of learning to run well also seen from the results of the assessment of learning outcomes which reached a percentage of 75%.